Performance of an integrated algal pond for treatment of domestic sewage: a process audit - Dube, Anele (Rhodes University, Faculty of Science, Institute for Environmental Biotechnology, 2020)
Integrated algae pond systems (IAPS) are energy efficient, robust, passive systems that use the principles of fermentation, photosynthesis and microbial metabolism to remediate wastewater, producing a good quality effluent with reuse potential. In addition to the treatment of wastewater, IAPS have the ability to generate two additional product streams viz. biogas and biomass. The latter adds to the attractiveness of the system. However, the implementation of this technology, like many passive systems, has remained limited at a commercial scale, and the inclination is still towards grey technologies. The aim of this research was to investigate the capabilities and potential of a demonstration-scale IAPS and use results obtained to establish a process audit framework. The aspects considered for the audit included performance efficiency, effluent water quality, biomass composition, quantity and productivity within the ponds, and cost analysis of operation and maintenance over a 9-year period. Plant performance was closely monitored during the course of the study and this led to a review of previously adopted plant management strategies. Troubleshooting exercises were also carried out when plant performance declined. Results showed that IAPS efficiently reduced standard water parameters with the exception of pH, dissolved oxygen, and nitrate whose values increased from raw influent to final effluent. The following water quality parameters were established for the final effluent: total suspended solids 55 ± 7.1 mg. L-1 (n = 28); chemical oxygen demand 94.1 ± 10.6 mg. L-1 (n = 28) (after removal of algae); pH 9.9 ± 0.01 (n = 26); ammonium nitrogen 1.7 ± 0.3 mg. L-1 (n = 25); nitrate 3.3 ± 0.6 mg. L-1 (n = 25); ortho-phosphate 1.6 ± 0.2 mg. L-1 (n = 25); electrical conductivity 98.7 ± 2.0 mS m-1 (n = 26) and faecal coliforms (per 100 mL) 1482.6 ± 636.0 (n = 24). The final effluent measured consistently high chemical oxygen demand and total suspended solids, however close analysis showed that total suspended solids could be controlled by increasing the frequency of removal of settled biomass within the settling ponds. Biomass produced contained microalgae, bacteria, metazoa, and protozoa. The biomass productivity achieved was as high as 130.6 kg ha-1 d-1; however, about 33% was lost to the final effluent due to inadequate settling. Results obtained during the course of this study and outcomes of earlier work on IAPS are taken as the baseline to determine parameters needed for the development of the process audit framework. Techniques utilised to derive the blue print process audit protocol for IAPS included a turtle diagram, a flow diagram and a checklist. Attention to plant management proved vital in determining overall performance. Cost, including operating and maintenance, of treating water using the demonstration scale system on a per person equivalent per year basis was determined as ZAR 123.87 (where, ZAR to USD = 0.07).
Keywords: Water -- Purification; Sewage -- Purification -- Anaerobic treatment; Algae -- Biotechnology; Waste disposal -- South Africa; Integrated algae pond systems (IAPS)